The Effects of Work-Life Benefits on Employment Outcomes in Canada: A Multivariate Analysis - Tony Fang; Byron Lee; Andrew R. Timming; Di Fan (Institute of Labor Economics (IZA), 2019)
Using the longitudinal Workplace and Employee Survey of Canada, we examine the association between the provision of work-life benefits and various employment outcomes in the Canadian labour market. Whilst the theory of compensating wage differentials hypothesizes an inevitable trade-off between higher wages and non-wage benefits, the efficiency wage theory suggests otherwise. The empirical evidence broadly supports the efficiency wage theory, thus rejecting the compensating wage differentials theory. If bundled appropriately, it appears that work-life benefits are positively associated with increased wages, in addition to a greater number of promotions, enhanced employee morale in the form of job satisfaction, and improved employee retention. The study concludes that organizations and employees can both profit when work-life benefits are offered.
Keywords: J32; J33; J38; 330; compensating wage differentials; efficiency wage theory; job satisfaction; promotion; wages; work-life benefits